Sobre a beleza como símbolo da moralidade em Kant - Guimarães, Rômulo Eisinger (2016)
In the Critique of the Power of Judgment Kant is concerned with the problem of Beauty s transcendental philosophy, seeking the possibility of a universally valid, a priori and necessary aesthetic judgment. The strategy adopted by the author starts by defining what the Beauty is not (in this case, a judgment of knowledge). Among other things, the complacency in Beauty is distinguished from complacency in Good, being the former disinterested, whereas the latter has an interest in the existence of the judged object. This difference is already made in the opening paragraphs of the first book of the Analytic of the Beauty. Nevertheless, insofar as Kant advances in his analysis of the feeling of the Beauty (and later, the Sublime), the author suggests that the separation between an aesthetic judgment (of the Beauty) and a moral judgment (of the Good) is not necessarily abrupt and sometimes such judgments constitute an ambiguous relationship. The work to be done intend to investigate the sinuosity of the Kantian discourse developed along the third Critique about the problem of the Beauty and the Good, especially the apparent change in Kant s argument at the §§16 and 17, and affirmation of the "Beauty as a Symbol of Morality" [KU, B253] in § 59 of this book.